The Second Punic War: The Spanish Theater of Operations - Omarkanova Asel Omarkanovna; Pronin Egor Dmitrievich (Progress in Science, 2025)
The second Punic War (218-201 BC) became one of the most famous, large–scale conflicts of antiquity, in which two great powers clashed - the once great trading power of Carthage and the growing Roman Republic. Traditionally, the focus of this topic has always been on Hannibal's passage through the Alps and his invasion of Rome, his legendary victories, that is, the main focus is on the Italian theater of operations, ignoring Spain, which was of key importance, namely strategic importance in this war.